The state of the Hungarian ornamental horticulture industry, recommendations for development - Orlóci, László (Acta Agraria Debreceniensis, 2018)
R&D and innovative technologies are required in the EU for being competitive on the world market. Education and professional co-ordination is vitally important, as well as maintenance and development of our genetic bases.